2019
DOI: 10.1111/jce.13868
|View full text |Cite
|
Sign up to set email alerts
|

Renal sympathetic denervation improves clinical outcomes in patients undergoing catheter ablation for atrial fibrillation and history of hypertension: A meta‐analysis

Abstract: Background Currently, there is limited data regarding the impact of adjunctive renal sympathetic denervation (RSDN) with pulmonary vein isolation (PVI) in hypertensive patients with atrial fibrillation (AF). Methods A comprehensive literature search for studies comparing RSDN + PVI vs PVI alone for AF and history of hypertension until 1 January 2019 was performed. The results were expressed as risk ratio (RR) for the categorical variables and mean difference (MD) for the continuous variables with 95% confidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Feyz et al, in the AFFORD study, demonstrate that RSD might be able to decrease AF burden in hypertensive patients, determining a positive effect on quality of life 75 . Finally, same clinical result was recently observed in a metanalysis of six eligible (four randomized and two prospective nonrandomized) studies showing that this combined approach significantly decreased the risk of AF recurrence when compared with PVs isolation alone 76 . Nevertheless, RSD eliminates sympathetic postganglionic axons that can present rapid reinnervation.…”
Section: Non‐direct Cardiac Neuromodulationmentioning
confidence: 68%
“…Feyz et al, in the AFFORD study, demonstrate that RSD might be able to decrease AF burden in hypertensive patients, determining a positive effect on quality of life 75 . Finally, same clinical result was recently observed in a metanalysis of six eligible (four randomized and two prospective nonrandomized) studies showing that this combined approach significantly decreased the risk of AF recurrence when compared with PVs isolation alone 76 . Nevertheless, RSD eliminates sympathetic postganglionic axons that can present rapid reinnervation.…”
Section: Non‐direct Cardiac Neuromodulationmentioning
confidence: 68%
“…AFFORD study showed that patients with AF and hypertension undergoing RDN benefited in terms of blood pressure control and AF burden reduction [ 193 ]. A small ( N = 432) meta-analysis by Atti V et al demonstrated that RDN plus PVI is superior to PVI alone in reducing post-ablation arrhythmia recurrence in patients with AF (paroxysmal or persistent) and concomitant hypertension (RR: 0.58; 95% CI: 0.47–0.72; p < 0.00001) [ 194 ].…”
Section: Therapeutic Perspectivesmentioning
confidence: 99%
“…However, cardiac sympathetic denervation (CSD) is often associated with adverse events 8 . Catheter‐based renal sympathetic denervation (RSDN) (similar to CSD) has recently emerged as a less invasive modality for modulating the autonomic nervous system—and lately, has been increasingly used for the treatment of resistant hypertension and atrial fibrillation 9 . Furthermore, RSDN has been recently described as a possible management approach in patients with recurrent VA refractory to antiarrhythmic drugs and catheter ablation (CA).…”
Section: Introductionmentioning
confidence: 99%